Cover Feature: Development of an SBU‐Based Mechanochemical Approach for Drug‐Loaded MOFs (Eur. J. Inorg. Chem. 10/2020). Issue 10 (9th March 2020) - Nawrocki, Jan; Prochowicz, Daniel; Wiśniewski, Andrzej; Justyniak, Iwona; Goś, Piotr; Lewiński, Janusz
Abstract : The Cover Feature shows an efficient one‐step mechanochemical approach for drug‐loaded MOFs. A proof of concept combines the mechanosynthesis of HKUST‐1 and the encapsulation of ibuprofen, as a model drug molecule, by a one‐pot reaction involving a pre‐assembled [Cu2 (rac‐IBU)4 ] cluster. This novel method offers new opportunities for the encapsulation of bioactive molecules in MOFs. More information can be found in the Communication by J. Lewiński et al.